Shear behavior of steel I-girder with stiffened corrugated web, Part I: Experimental study. (July 2019) - Wang, Sihao; He, Jun; Liu, Yuqing
Abstract: The shear stability of steel webs near the support section for long-span composite girders with corrugated steel webs is one of the main control factors for structural safety, which should be paid special attention to. Generally, concrete is poured on the inner side of corrugated steel webs to improve its shear stability, but encased concrete increases the weight of the girder, raises the difficulty of the construction process, and reduces the efficiency of the prestressing application. This paper proposes a new type of stiffened corrugated steel webs at the support area by adopting vertical or/and horizontal stiffeners instead of encased concrete. In order to explore the shear performance of proposed stiffened corrugated steel webs, experimental and numerical investigations were carried out in the present paper and the companion paper[1], respectively. Four steel I-girders with corrugated webs considering different stiffener arrangements were designed and tested under shear loading. The failure modes, shear strength and stiffness, strain distributions were obtained and analyzed in detail. The test results show that all specimens failed due to interactive shear buckling of corrugated steel web; shear buckling occurred between horizontal stiffeners and bottom flange for horizontal stiffened corrugated steel webs, but extended to the entire height for vertical stiffened corrugated steel webs, the stiffeners distorted associated with the deformation of corrugated steel web. Shear strength of corrugated steel webs can be improved by vertical and horizontal stiffeners. The vertical stiffeners do not affect the "accordion effect" of corrugated steel webs, but the horizontal stiffeners increase the axial stiffness of corrugated steel web in local area and resist bending moment together with top and bottom flanges. The shear strain of stiffened corrugated steel web still distributes uniformly along the height of the web. All the experimental results are then employed in the companion paper for the validation of finite element method and the evaluation of existing analytical models for predicting shear strength of un-stiffened and stiffened corrugated steel webs. Highlights: We proposed a new type of stiffened corrugated steel web. Shear behavior of steel I-girder with stiffened corrugated webs has been experimentally investigated. Shear strength of corrugated steel web can be improved by vertical and lateral stiffeners. Lateral stiffeners increase the axial stiffness of corrugated steel webs in local area.